Depression And Quality of Life Among Type-2 Diabetes Mellitus Patients: A Case Control Study - Suleman Shareef Mahammad; A Indira; Visweswara Rao Guthi; Alex Viji; G Aruna; Katari Kantha; J Jasmine (Medsci Publications, 2022)
Background: Diabetes is accompanied by a distinct decreased in subject's quality of life (QOL) and it shows to elevated disability-adjusted life years than most diseases. Depression shows the degrade QOL and is associated with wretched treatment outcomes and lesser the glycaemic control in diabetes. Objective of this study is to study the association between Quality of Life (QoL) and depression among type2 diabetes mellitus in Andhra Pradesh.  Methodology: The present study is a case control study. There were 300 participants including 150 type2 diabetes mellitus patients, & 150 healthy individuals (age and gender matched) were also selected as a control to meet the purpose of the study. Subjects age range was set between 35-65 years. Beck depression inventory (BDI-II) and WHO quality of life scale (QOL BREF) were used for data collection, SPSS-26(v). Results: The study findings showed that significant but negative relation between depression scores and quality of life. 65% have Poor Quality of life & 57% have high depression in Diabetes Patients. 54% have good Quality of life & 78% have Mild Depression in Healthy Individuals. Conclusion: It is concluded that association between depression and sub-scales of quality of life indicating that high depression scores may lead to lower physical and psychological health impacting social relationship and environmental health.